CD73 is dispensable for the regulation of inflationary CD8+ T-cells after murine cytomegalovirus infection and adenovirus immunisation - Sims, S; Colston, J; Emery, V; Klenerman, P (Public Library of Science, 2014)
The ecto-5'-nucleotidase (CD73) is expressed by T-cell subsets, myeloid derived suppressive cells and endothelial cells. It works in conjunction with CD39 to regulate the formation and degradation of adenosine in vivo. Adenosine has previously been shown to suppress the proliferation and cytokine secretion of T-cells and recent evidence suggests that inhibition of CD73 has the potential to enhance T-cell directed therapies. Here we utilised a CD73 knockout mouse model to assess the suppressive ability of CD73 on CD8+ T-cell classical memory and memory “inflation”, induced by murine cytomegalovirus (MCMV) infection and adenovirus immunisation. We show that CD73 is dispensable for normal CD8+ T-cell differentiation and function in both models. Thus CD73 as a suppressor of CD8+ T-cells is unlikely to play a deterministic role in the generation and functional characteristics of antiviral memory in these settings.